DETERMINAN PENYERAPAN ANGGARAN DENGAN KOMITMEN ORGANISASI SEBAGAI MODERATING VARIABLE - Ahmad Sirin; Indarto Indarto; Wyati Saddewisasi (Universitas Semarang, 2020)
This study aims to analyze the effect of budget planning, human resource competence and budget evaluation on budget absorption through organizational commitment as a moderating variable. The population in this study were 35 district / city offices of the Ministry of Religion in Central Java and 1 Regional Office of the Ministry of Religion, Central Java Province. The sample was 106 respondents. The respondents are financial management employees, namely planners, commitment makers, expenditure treasurers and financial management staff in 36 work units within the Regional Office of the Ministry of Religion, Central Java Province. Data collection was carried out through a survey using a questionnaire distributed to respondents. Data were analyzed using partial least square (PLS) with SmartPLS tools. The results showed that budget planning, human resource competence and budget evaluation had a positive and significant effect on the level of budget absorption. The organizational commitment variable does not strengthen the influence of budget planning, human resource competence and budget evaluation on budget absorption in the work unit within the Regional Office of the Ministry of Religion of Central Java Province.Penelitian ini bertujuan menganalisis pengaruh perencanaan anggaran, kompetensi sumber daya manusia dan evaluasi anggaran terhadap penyerapan anggaran melalui komitmen organisasi sebagai variabel moderasi. Populasi dalam penelitian ini adalah 35 Kantor Kementerian Agama kabupaten/kota di Jawa Tengah dan 1 Kantor Wilayah Kementerian Agama Provinsi Jawa Tengah. Sampel sebanyak 106 responden. Responden penelitian adalah pegawai pengelola keuangan, yaitu Perencana, Pejabat Pembuat Komitmen, Bendahara Pengeluaran dan Staf Pengelola Keuangan pada 36 satuan kerja pada lingkup Kantor Wilayah Kementerian Agama Provinsi Jawa Tengah. Pengumpulan data dilakukan melalui survei dengan menggunakan kuesioner yang dibagikan kepada responden. Data dianalisis dengan menggunakan partial least square (PLS). Hasil Penelitian menunjukkan bahwa perencanaan anggaran, kompetensi sumber daya manusia dan evaluasi anggaran berpengaruh positif dan signifikan terhadap tingkat penyerapan anggaran. Variabel komitmen organisasi tidak memperkuat pengaruh perencanaan anggaran, kompetensi sumber daya manusia dan evaluasi anggaran terhadap penyerapan anggaran pada satuan kerja lingkup Kantor Wilayah Kementerian Agama Provinsi Jawa Tengah.